APOE-ε4 Genotype and Dementia Before and After Transient Ischemic Attack and Stroke: Population-Based Cohort Study. Issue 3 (March 2020) - Pendlebury, Sarah T.; Poole, Debbie; Burgess, Annette; Duerden, Julia; Rothwell, Peter M.
Abstract : Background and Purpose—: APOE-ε4 genotype is a risk factor for sporadic Alzheimer disease and reduced recovery from brain injury. Since data on APOE genotype and dementia associated with transient ischemic attack/stroke are sparse, we determined the associations in a longitudinal population-based cohort. Methods—: All patients with transient ischemic attack or stroke (2002–2012) in a defined population of 92 728 OxVASC (Oxford Vascular Study) had follow-up to 5-years. Pre-event and incident postevent dementia were ascertained through direct patient assessment and follow-up, supplemented by review of hospital/primary care records. Associations between pre- and post-event dementia and APOE genotype (ε4/ε4-homozygous and ε4/ε3-heterozygous versus ε3/ε3) were examined using logistic regression and Cox regression models, respectively, adjusted for age, sex, education, cerebrovascular burden (stroke severity, prior stroke, white matter disease), diabetes mellitus, and dysphasia. Results—: Among 1767 genotyped patients (mean/SD age, 73.0/13.0 years, 901 [51%] male, 602 [34%] transient ischemic attack), 1058 (59.9%) were APOE-ε3/ε3, 403 (22.8%) were ε4/ε3 and 30 (1.7%) were ε4-homozygous. Homozygosity was associated with both pre-event (adjusted odds ratio, 5.81 [95% CI, 1.93–17.48]; P =0.002) and postevent dementia (adjusted hazard ratio, 3.64 [95% CI, 1.90–7.00]; P <0.0001). Association with postevent dementia was maintained after further adjustment for baseline cognitive impairment (hazard ratio, 2.41 [95% CI, 1.19–4.89]; P =0.01). There were no associations overall between ε4/ε3 and pre-event dementia (adjusted odds ratio, 1.47 [95% CI, 0.88–2.45]; P =0.14) or postevent dementia (hazard ratio, 1.11 [95% CI, 0.84–1.48]; P =0.47). Conclusions—: In patients with transient ischemic attack and stroke, APOE-ε4 homozygosity was associated with both pre- and post-event dementia. Associations were independent of cerebrovascular burden and may be mediated through increased neurodegenerative pathology or vulnerability to injury. Abstract : Supplemental Digital Content is available in the text.